When art meets fashion: How Louis Vuitton avoided the commodity trap. Issue 2 (7th January 2014) - Unknown
Abstract : Purpose: – Reviews the latest management developments across the globe and pinpoints practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – Succeeding in business is often down to creating products that are unique and thus distinct from competitor offerings. Firms who achieve this are able to effectively target specific consumer segments, gain a healthy market share and charge a price premium. The luxury market is a fine example. Recent years has brought rapid expansion and increased variety of offerings. It is a sector where the brand is a huge asset that conveys symbolic and affective value. Brand reputation is also crucial to the success of upscale differentiation. Growth is not all positive though. The luxury sector has become industrialized to the extent that global brands have emerged and developed sizeable retail networks to provide the necessary support. Many companies have positioned their brands in mid-market and consequently offer comparable luxury items at a significantly lower cost. Such developments have made it increasingly difficult for luxury brand manufacturers to sustain product uniqueness and justify a high price. Practical implications: – Provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to digest format.